Analysis of the Need for English Textbooks for Mathematics Education Students at UNIMUDA Sorong - Dwi Pamungkas (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
The purpose of this study was to find out the needs of students regarding Interactive Learning-based mathematics textbooks in English. The method used in this research is descriptive qualitative. The subjects of this study were 4 Mathematics Education Students at UNIMUDA Sorong who had taken an English course. Data collection techniques using interviews and questionnaires. The results of the study show that students want English teaching materials that are easy to understand, communicative, and interactive.